A processual perspective on whole-class- scaffolding in business education - Rico Hermkes; Gerhard Minnameier; Manon Heuer-Kinscher (International Journal for Research in Vocational Education and Training (IJRVET), 2022)
Context: Scaffolding is a form of process-adaptive learning support that is relevant in numerous contexts, including informal learning, workplace learning as well as school teaching. While scaffolding can be well conceptualised for individual learning situations (especially for tutoring situations), there is a difficulty in measuring process adaptivity in heterogeneous learning groups, such as school classes. Approach: In this paper, we develop a measurement method that targets the deep structure of teaching and learning in whole class settings. Processes of shared knowledge constructions are taken into account, since whole-class-scaffolding (WCS) means to shape and develop common or joint knowledge spaces rather than to scaffold a multitude of individual construction processes at the same time. To achieve a coding procedure for WCS interactions, we integrate scaffolding principles and principles of dialogic teaching and explicated a set of rules that can be correlated to the quality of WCS-episodes rated on distinct Likert scales. Results: The measurement method developed in the paper provides a solution to the problem of how to measure process-adaptive learning support that is not only related to individual learners, but is directed at a heterogeneous group of learners in which different support needs may be present simultaneously. The coding procedure systematically links scaffolding principles and principles of dialogic teaching and enables us to capture the dynamics of teaching and learning processes in larger group settings. In this respect, concepts such as joint- and common space, representing entities to which WCS refers, are operationalised. Conclusions: When methods for measuring the dynamics of teaching and learning processes are available, research on instructional support is no longer limited to global ratings of whole learning units. Furthermore, the codings allow for a more fine-grained analysis of trajectories of scaffolding interactions. Such an analysis reveals information about local specifics of WCS that can explain further learning differences between students and that can be used to derive implications for effective instructional techniques.
Keywords: 330; Scaffolding; Dialogic Teaching; Shared Knowledge Construction; Adaptivity; VET; Vocational Education and Training